The Impact and Evolution of COVID-19 on Liver Transplant Recipients Throughout the Pandemic “Waves” in a Single Center - Clara Fernández Fernández; Blanca Otero Torrón; Mercedes Bernaldo de Quirós Fernández; Rafael San Juan Garrido; Cristina Martín-Arriscado Arroba; Iago Justo Alonso; Alberto Alejandro Marcacuzco Quinto; Óscar Caso Maestro; Félix Cambra Molero; Oana Anisa Nutu; Jorge Calvo Pulido; Alejandro Manrique Municio; et al. (Viruses)
Liver transplant recipients (LTRs) have been considered a population group that is vulnerable to COVID-19 as they are chronically immunosuppressed patients with frequent comorbidities. This study describes the course of the SARS-CoV-2 disease from February 2020 to December 2023 along seven pandemic “waves”. We carried out an observational study on 307 COVID-19 cases in a cohort of LTRs with the aim of evaluating the changes in the disease characteristics over time and determining the risk factors for severe COVID-19. An older age and serum creatinine level ≥ 2 mg/dL were found to be risk factors for hospital admission and respiratory failure. The use of calcineurin inhibitors was a protective factor for death, hospitalization, and respiratory failure from COVID-19. One hundred percent of patients who died (N = 12) were on mycophenolate mofetil, which was a determinant for respiratory failure. Azathioprine was associated with admission to the intensive care unit (ICU) and with invasive mechanical ventilation (IMV). Vaccination was a protective factor for hospitalization, respiratory failure, and mortality. The severe COVID-19 rate was higher during the first five waves, with a peak of 57.14%, and the highest mortality rate (21.43%) occurred in the fourth wave. The IMV and ICU admission rates did not show significant differences across the periods studied.